2000
DOI: 10.1038/sj.bjp.0703255
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of apoptosis by glucocorticoids in glomerular endothelial cells: effects on proapoptotic pathways

Abstract: 1 Tumour necrosis factor-a (TNF-a)-and lipopolysaccharide (LPS)-induced apoptosis of bovine glomerular endothelial cells is now recognized as an important part in the pathogenesis of glomerulonephritis characterized by early mitochondrial cytochrome c release, mitochondrial permeability transition, Bak protein upregulation, Bcl-X L protein downregulation and caspase-3 activation. 2 Co-treatment of cells with 10 nM dexamethasone and TNF-a or LPS blocked roughly 90% of apoptotic cell death in glomerular endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 54 publications
2
30
0
2
Order By: Relevance
“…The reported increased expression of Bcl-x L mRNA in human myeloid leukemic cells required 24 h of hormone treatment (48), whereas we clearly detected up-regulation of Bcl-x L after 2 h of dexamethasone treatment. Subsequent studies by other groups have also demonstrated the importance of increasing Bcl-x L expression for the inhibition of apoptosis by glucocorticoids in a variety of cell types (3,8,31,49). However, none of these reports identified the mechanism by which GR might control Bcl-x expression.…”
Section: Discussionmentioning
confidence: 93%
“…The reported increased expression of Bcl-x L mRNA in human myeloid leukemic cells required 24 h of hormone treatment (48), whereas we clearly detected up-regulation of Bcl-x L after 2 h of dexamethasone treatment. Subsequent studies by other groups have also demonstrated the importance of increasing Bcl-x L expression for the inhibition of apoptosis by glucocorticoids in a variety of cell types (3,8,31,49). However, none of these reports identified the mechanism by which GR might control Bcl-x expression.…”
Section: Discussionmentioning
confidence: 93%
“…In breast and other origin cancer cells, the synthetic glucocorticoid, dexamethasone (DEX), induces the expression of genes frequently associated with protection against cell apoptosis, such as Bcl-xL, Bak, SGK-1 and MKP-1 [16,17,23,24,57]. Concomitantly, DEX also reinforces its survival effect by the downregulation of pro-apoptotic genes, such as Bid, TRAIL and GR-dependent gene tissue plasminogen activator (tPa) [24].…”
Section: Gr and Cell Apoptosismentioning
confidence: 98%
“…GCs have been shown to specifically inhibit chemotherapeutic anti-tumor activities in human breast preclinical model by decreasing cellular apoptosis resulting in larger tumor volumes [15-18, 23, 24]. mRNA expression analysis in xenograft tumors, excised from mice exposed to systemic GCs treatment, demonstrated an upregulation of anti-apoptotic genes, such as Bcl-xL, Bak, SGK-1, or MKP-1 [16,17,23,25,57]. Interestingly, MKP-1 overexpression has also been observed in primary human breast and prostate tumors context [87,88].…”
Section: Gc-induced Chemoresistance In Breast Cancermentioning
confidence: 99%
“…49 TNF␣-induced injury is mediated via both its receptors, TNFR1 and TNFR2, with clear evidence for a proapoptotic role in renal tissue. 33,49,50 In this study we identify TIMP3 as a critical negative regulator of renal TNF␣ activity. In the absence of the negative regulatory function of TIMP3, TNF␣ further triggers apoptosis and inflammation, as also reported in a wide range of pathophysiological conditions.…”
Section: Increased Timp3 Levels In Human Kidney Diseasementioning
confidence: 99%